Nazhir Capacity Analysis and Cooperation in Productive Waqf Management - Muhammad Ash Shiddiqy (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2022)
Abstract: Waqf is an economic tool that can bring prosperity to the community. Therefore, good and proper management is required to realize the best interests of wakaf property. As the manager and developer of waqf property, Nazhir must have the ability and skills to manage waqf property. For this reason, special standardization is required to obtain a capable Nazhir based on the wealth of the waqf under management. When the management of the wakaf property works well and produces the best benefits, then these benefits can be used as the beneficiaries of the wakaf property to prosper the community. In the Law on Waqf No. 41 of 2004 and Government Regulation No. 42 of 2006 it has been stated about the responsibilities, roles, and functions of Nazhir. In addition to the law, there are also minimum requirements and abilities that an individual or group of Nazhir must possess. It is hoped that Nazhir in the future will have special abilities. Even though he did not have special skills, Nazir must have a strong desire to learn something related to the management, management and development of Waqf.                                                           Abstrak: Wakaf merupakan alat ekonomi yang dapat membawa kesejahteraan bagi masyarakat. Oleh karena itu, diperlukan pengelolaan yang baik dan benar untuk mendapatkan manfaat yang terbaik dari harta wakaf. Sebagai pengelola dan pengembang harta wakaf, Nazhir harus memiliki kemampuan dan keterampilan dalam mengelola harta wakaf. Untuk itu diperlukan standarisasi khusus untuk mendapatkan nazhir yang mumpuni berdasarkan harta wakaf yang dikelolanya. Ketika pengelolaan harta wakaf dapat berjalan dengan baik dan menghasilkan keuntungan yang sebesar-besarnya, maka manfaat tersebut dapat dijadikan sebagai penerima manfaat harta wakaf untuk mensejahterakan masyarakat. Pada Undang- Undang Tentang Wakaf No 41 Tahun 2004 dan Peraturan Pemerintah No 42 Tahun 2006 telah disampaikan tentang tanggungjawab, peran, serta fungsi Nazhir. Selain undang-undang, ada juga persyaratan dan kemampuan minimum yang harus dimiliki oleh individu atau kelompok Nazhir. Diharapkan Nazhir di masa depan akan memiliki kemampuan khusus. Meski tidak memiliki keahlian khusus, Nazir harus memiliki keinginan yang kuat untuk mempelajari sesuatu yang berkaitan dengan pengelolaan, pengelolaan dan pengembangan Wakaf.